THE USE OF THE IDEF0 STANDARD IN PREPARATION FOR PHARMACEUTICAL DEVELOPMENT - S. A. Rozhnova; A. V. Tsypkina; O. S. Belokhvostova (Разработка и регистрация лекарственных средств, 2019)
The article presents information on the use of the IDEF0 standard in process visualization pharmaceutical development analytical stage.